Traditional Food Packaging Redesign to Expand Target Market Onde-Onde Gandoem Njonja Moeda in BEDA’KAN 11 - Stefanny Kusuma; Brian Alvin Hananto (IMATYPE: Journal of Graphic Design Studies, 2023)
Onde-Onde Gandoem Njonja Moeda is one of the Small-to-Medium Enterprises affected by the COVID-19 outbreak in Indonesia. In collaboration with Asprodi DKV and DJKI in the BEDA'KAN event, the authors made a proposal for a new packaging design for Njonja Moeda with the expectation of solving existing problems and fulfilling their intention. The activity was carried out by following the pre-design, design, and post-design framework, resulting in two alternative packaging, which was then selected to be finalized and printed. The final approved design is then being published in a live Zoom presentation meeting on March 26th, 2022.